2007
DOI: 10.1080/10238160601025138
|View full text |Cite
|
Sign up to set email alerts
|

Neutron activation analysis for studying Cr uptake in the blue-green microalga Spirulina platensis

Abstract: Exposure of Spirulina platensis cells to Cr(III) and Cr(VI) showed that unlike other organisms this bluegreen alga demonstrates a protective ability against Cr(VI). In laboratory experiments, the less toxic Cr(III) was absorbed much more readily than the more toxic Cr(VI). Colorimetric and EPR tests indicated that higher oxidation states of Cr are not formed following the accumulation of Cr(III) in Spirulina platensis cells. Control of the protein content and cytological study of the alga cells indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Blue-green algae (Cyanophyta) contain three orders: Chroococcales, Chamaesiphonales, and Hormogoneales; of which Chroococcales separates into two families-Chroococcaceae and Entophysalidaceae. 258,259 These two families can be distinguished from their ability to form colonies in their natural habitat, and are considered photoautotrophic, unicellular bacteria. 258,259 Blue-green algae have been widely used to generate a wide range of NPs, as shown in Table 5.…”
Section: Blue-green Algal-driven Nps Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Blue-green algae (Cyanophyta) contain three orders: Chroococcales, Chamaesiphonales, and Hormogoneales; of which Chroococcales separates into two families-Chroococcaceae and Entophysalidaceae. 258,259 These two families can be distinguished from their ability to form colonies in their natural habitat, and are considered photoautotrophic, unicellular bacteria. 258,259 Blue-green algae have been widely used to generate a wide range of NPs, as shown in Table 5.…”
Section: Blue-green Algal-driven Nps Biosynthesismentioning
confidence: 99%
“…258,259 These two families can be distinguished from their ability to form colonies in their natural habitat, and are considered photoautotrophic, unicellular bacteria. 258,259 Blue-green algae have been widely used to generate a wide range of NPs, as shown in Table 5.…”
Section: Blue-green Algal-driven Nps Biosynthesismentioning
confidence: 99%
“…Timiriazev Institute for Plant Physiology of the Russian Academy of Sciences was used. The cultivation conditions for S. platensis cells in standard water-salt nutrient medium are described elsewhere [13,14]. After 5-day cultivation, cells of S. platensis were separated from the culture broth by centrifugation (12,000 g) for 20 min, and then the biomass was washed twice with sterile distilled water.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In our earlier investigations, S. platensis was used as a matrix for the development of new pharmaceutical substances [13][14][15][16]. The elemental content of the initial biomass of Spirulina was studied using the neutron activation analysis; it was shown that the concentrations of some toxic elements in the biomass of S. platensis do not exceed permissible levels [14].…”
Section: Introductionmentioning
confidence: 99%